Study of Solar Energy Potential using CMP6 Pyranometer at Nepalgunj, Nepal - KC, Bed Raj; Gurung, Shekhar (Journal of Advanced Academic Research, 2017)
The global solar radiation (GSR) is measured at the horizontal surface since 2011 using calibrated CMP6 Pyranometer at Nepalgunj which is located at an altitude 150m above sea level. This paper explains the daily, monthly and seasonal variation of global solar radiation and also compares temperature with global solar radiation. The average temperature in Nepalgunj varies between 44°C (it is hottest from May through July) and 30°C, although during winter (November-January) it can reach 4°C. The annual average daily global solar radiation is about 12.9MJ/m2/day which is sufficient to promote active and passive solar energy technology in Nepalgunj and other similar geographical locations.